DEVELOPMENT, DELIVERY AND EVALUATION OF MICRO-CERTIFICATE MENTAL HEALTH AMBASSADORSHIP COURSE - Tahir, Tayyeb; Muchungi, Kendi; Iqbal, Maria; Njoroge, Willie; Maina, Rachel; Bosire, Edna Bosire; Merali, Zul (Journal of Pakistan Psychiatric Society, 2023)
Mental illnesses can impact anyone. However, those who suffer from mental ill health can face stigma contributing to a barrier in help-seeking behaviour. The Brain and Mind Institute, at the Aga Khan University (BMI AKU) aims to create a small ‘army’ of mental health ambassadors for mental health awareness, identification, and referral for those in need of help for their mental well-being. This is a narrative of designing, approving, standardising, delivering, evaluating and a proposing future evolution of a unique Micro-certificate Mental Health Ambassadorship course.